Regional Patterning of Adult Neurogenesis in the Homing Pigeon’s Brain - Mehlhorn, Julia; Niski, Nelson; Liu, Ke; Caspers, Svenja; Amunts, Katrin; Herold, Christina (Frontiers in Psychology, 2022)
In the avian brain adult neurogenesis has been reported in the telencephalon of several species, but the functional significance of this trait is still ambiguous. Homing pigeons (Columba livia f.d.) are well-known for their navigational skills. Their brains are functionally adapted to homing with e.g. larger hippocampi. Up to now, no comprehensive overview of adult neuro- and gliogenesis and no studies of different stages of cell proliferation and spatial distribution of newly generated cells in the telencephalon of homing pigeons exists, although comprehensive analyses in various species will lead to a higher understanding of the fundamentals of adult neurogenesis. Definitely, this will provide a better framework to investigate the functional significance of adult neurogenesis in the future. Here, adult, free flying homing pigeons were treated with 5-bromo-deoxyuridine (BrdU) to label newborn cells. Brains were dissected and immunohistochemically processed with several markers (GFAP, Sox2, S100b, Tbr2, DCX, Prox1, Ki67, NeuN, Calbindin, Calretinin) to study different stages of neurogenesis in a quantitative and qualitative way. Therefore, proliferating and newborn cells were analyzed along the anterior-posterior axis. The analysis proved the existence of different neuronal maturation stages and showed that proliferating cells were widely and regionally unequally distributed. The most newborn cells were found in the intercalated hyperpallium and the hippocampal formation. Highest numbers of proliferating cells were detected in the nidopallium. Additionally, the number of newborn glial cells exceeded the number of newborn neurons. Individual structures (e.g. intercalated hyperpallium, nidopallium) showed further variations along the anterior-posterior axis. Double labelled neuronal cells with several proliferative markers were found and indicate, for example, a state of proliferation (DCX/Ki67), of rest (BrdU/DCX), or of transformation (Calbindin/Calretinin) The different stages of cell proliferation and the distribution of maturing cells in the forebrain support the idea that there is a functional specialization, respectively, that there is a link between brain-structure and function, species-specific requirements and adult neurogenesis. The high number of immature neurons also suggests a high level of plasticity, which points to the ability for rapid adaption to environmental changes through additive mechanisms. Furthermore, we discuss a possible influence of adult neurogenesis on spatial cognition.